2005
DOI: 10.1079/bjn20041297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subthalamic nucleus deep brain stimulation and levodopa on energy production rate and substrate oxidation in Parkinson's disease

Abstract: Patients with Parkinson's disease (PD) often lose weight, but after subthalamic nucleus deep brain stimulation (STN-DBS), they gain weight. We compared daily energy intake (DEI), resting energy expenditure (REE) and substrate oxidation rates (measured by indirect calorimetry) in nineteen STN-DBS-treated patients (Group S), thirteen others on pharmacologic treatment by levodopa (Group L) and eight control subjects. We also determined the acute effects of STN-DBS and levodopa on REE and substrate oxidation rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 26 publications
9
60
5
Order By: Relevance
“…Whether this effect is exclusively due to the decrease in energy expenditure consecutive to the improvement of motor symptoms is still unknown. An additional effect on energy metabolism by current diffusion to the hypothalamus or motivational change by activation of the limbic circuit of the basal ganglia may be hypothesized (Perlemoine et al, 2005;Montaurier et al, 2007).…”
Section: Examples Of Studies On the Porcine Central Nervous Systemmentioning
confidence: 99%
“…Whether this effect is exclusively due to the decrease in energy expenditure consecutive to the improvement of motor symptoms is still unknown. An additional effect on energy metabolism by current diffusion to the hypothalamus or motivational change by activation of the limbic circuit of the basal ganglia may be hypothesized (Perlemoine et al, 2005;Montaurier et al, 2007).…”
Section: Examples Of Studies On the Porcine Central Nervous Systemmentioning
confidence: 99%
“…Furthermore, a reduction of the total daily dose of L -dopa may have an additional role, via probable lipolytic effects [11] , as well as a central effect on the satiety/appetite hypothalamic centers [12] . Improvement in mood and functional independence may also contribute to WG [5] .…”
mentioning
confidence: 99%
“…WG after DBS has been demonstrated in various studies [5][6][7] , but few have examined the etiopathogenetic mechanisms [6,7] . However, 'peripheral' and 'central' mechanisms are currently hypothesized.…”
mentioning
confidence: 99%
“…Body weight variation has been reported in many studies as a non-motor secondary effect of DBS-STN [7][8][9][10]. Studies have shown that weight loss in patients with PD before surgery is a continuous and progressive process that starts years before a formal diagnosis is made, and that surgery modifies this state [11][12][13][14]. Some authors have proposed that PD is associated with profound alterations in energy metabolism that are normalized after DBS-STN [13,15].…”
Section: Deep Brain Stimulation Of Subthalamic Nucleus (Dbs-stn) Offersmentioning
confidence: 99%